It's normal giving birth at home: The search for the revaluation of the home environment as an adequate space for the moment of childbirth (Research, Society and Development, 2021)
The objective of this study was to highlight the revaluation of the home environment as an adequate space for the moment of birth. This is a literature review of the bibliographic/narrative type, based on the exploratory dimension. The sources for searching the referentials involved the database of the dados Portal de Periódicos da Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (CAPES), the virtual library Scientific Electronic Library Online (SciELO) and the electronic search engine Google Scholar. The home as a place of care in childbirth brings several elements that favor one of the main requirements for the rescue of humanization in the birth process: the woman's autonomy. At home, she becomes an active subject of her birth, rescuing her own birth and control over her body, having the opportunity to act, to make her choices safely, without being inhibited. At home, the woman feels safe, surrounded by people who love her, being able to express her feelings and be authentic in her behaviors and behaviors. With this review, it appears that the home can be unique and an important space for care, because from the knowledge of the specific characteristics of this environment and its members, it is possible that the professionals who assist the pregnant woman/parturient to develop more contextualized care actions and effective.